Oil palm frond for the production of bioethanol - Lim Sheh Hong; Darah Ibrahim; Ibrahim Che Omar (2012)
In order to investigate the possibility of using oil palm frond (OPF) as biomass resource for alternative energy production, the chemical composition of OPF was examined. OPF used in this study contained 50.7% holocellulose. It was enzymatically hydrolyzed by Aspergillus niger USM AI1 in a solid substrate fermentation (SSF) and ethanol was produced from the hydrolyzates in a second fermentation with the yeast, Saccharomyces cerevisiae. The yield of fermentable sugars was 200.2 mg/ g substrate which contained 69.2% of glucose. The fermentable sugar obtained from OPF could be used by S. cerevisiae to produce ethanol. After 36 h of fermentation, the ethanol was about 23.1 g/L with 6% (w/v) of the fermentable sugar used as the carbon source in the fermentation medium at 30°C. Thus, this finding indicates that OPF can be used as suitable lignocellulosic material for the production of fermentable sugars through in-situ enzymatic hydrolysis under the SSF condition for second generation bioethanol production.